Comparison of letrozole associated antagonist protocol with other protocols in poor responder patients undergoing assisted reproductive treatment - Atilgan, R.; Kumbak, B.; Sahin, L.; Ozkan, Z. S.; Simsek, M.; Sapmaz, E. (Oxford Univ Press, 2012)
[Abstract Not Available]
28th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUL 01-04, 2012 -- Istanbul, TURKEY